Is Homicide a Turning Point in the Life of Perpetrators? A Narrative Analysis of the Life Stories of Marginalized and Middle-Class Male Homicide Offenders in Metropolitan Buenos Aires, Argentina - Di Marco, Martín Hernán (Qualitative Sociology Review, 2022)
This paper aims to analyze the relevance given to violent deaths and imprisonment by male homicide perpetrators in their biographical reconstructions. Drawing on narrative criminology, this study examines the offenders’ emic terms, rationalities, and stories. The analysis is based on seventy-three purposefully selected narrative-biographical interviews and field observations in prisons and homes of former convicts (2016-2020) in Metropolitan Buenos Aires, Argentina. The corpus was analyzed following an inductive thematic coding strategy using ATLAS.ti. Three central narratives about homicide and incarceration emerged: “opportunity,” “rock bottom,” and “disruptive.” For most, homicide was described as a biographical opportunity to rethink their lives, pursue new pathways, and “stabilize” a previously uncontrolled lifestyle. However, homicides perpetrated by respondents with higher socioeconomic status were disruptive events. Participants used stoic rationality—the positive appraisal of painful experiences—to structure their sense-making and stories of violence. This rationality permeated perpetrators’ presentations of themselves, their turning points and lived experiences, and the violence performed and suffered. This paper grapples with the widespread assumption that homicide is a radical change in the lives of offenders and questions the universal meaning of violent death. Performing violence is not only neutralized but is also seen as an expected and inaugural event in life stories, dependent on the worldviews of the social actors.